Protective Effect of Triphala Mediated by H2S Signaling Pathway in LPS-Induced RAW Macrophages - Shyam Sundar Shanker; Tiasha Dasgupta; Sharmila Hussain; H Annapoorni; Ramasamy Tamizhselvi (Journal of Pharmacy and Bioallied Sciences)
Introduction: MacrophagesHydrogen sulfide (H2 S), an endogenously produced gasotransmitter, is a wellknown inflammatory agent production successfully controlled with triphala in macrophages. Materials and method: The ELISA analysis revealed that triphala extracts suppress the protein expression of NFκB (p65) and downregulation of the CSE gene expression. Moreover, in the presence of propargylglycine (PAG) the expression of NFκB and CSE gene was further reduced. Results: These results suggest that triphala could be a potent antiinflammatory effect that could be used for the treatment of many inflammatory disorders, including periimplantitis.